PHYSIOLOGICAL RESPONSES OF JU-JITSU FIGHTING MALE COMPETITION IN THAILAND - Khemthong, Samanya; Khaosanit, Pattarawut; Apanukul, Suttikorn (Journal of Sports Science and Health, 2025)
Purpose This study aimed to examine the physiological responses before and after competition in Ju-Jitsu fighting male -62 kg. weight category. Methods The participants were eight male Ju-Jitsu Player aged 18–24 years, holding at least a brown belt, and competing in the -62 kg. category. They were purposively selected based on accumulated scores from five official competitions sanctioned by the Ju-Jitsu Association of Thailand. The player participated in five rounds of matches, from preliminary to final, totaling 16 matches. Physical fitness was assessed two days before the competition. Physiological responses—heart rate (HR), blood lactate concentration (BLC), and Peripheral oxygen saturation (SpO2). The differences between pre- and post-competition measurements (HR and BLC) were analyzed using the Paired Sample t-test. If the data were not normally distributed, the Wilcoxon Signed-Rank Test was employed (SpO2). The differences between winners and losers were analyzed using the Independent Sample t-test (HR and BLC). In cases where the data were not normally distributed, the Mann–Whitney U Test was used (SpO2). Statistical significance was set at p < 0.05. Results There were statistically significant differences (p < 0.05) in HR, BLC, and SpO2 before and after competition. HR increased by 57.46%, BLC by 92.48%, and SpO2 by 1.50%. When analyzed by match outcome, significant changes (p < 0.05) in all three variables were found in winners, while losers showed significant changes only in HR and BLC levels. No statistically significant differences were observed between winners and losers in any physiological variable before or after competition. However, winners demonstrated superior physical fitness in all aspects, handgrip strength, leg power, and upper- and lower-body muscular strength. Conclusion After the competition, Ju-Jitsu Players showed increased HR and BLC, while SpO2 decreased. This indicates that Ju-Jitsu is a high-intensity sport that relies heavily on anaerobic energy systems and rapid recovery ability. No significant physiological differences were observed between winners and losers, suggesting that both groups exerted maximal physical effort. Therefore, training should focus on enhancing recovery systems and improving lactate clearance to maintain performance in subsequent rounds of competition.